2009
DOI: 10.1016/j.jde.2009.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Existence and controllability results for nondensely defined impulsive semilinear functional differential inclusions

Abstract: MSC: 34A37 34A60 34G25 34K30 34K35 34K45 93B05 Keywords: Nondensely defined operator Impulsive semilinear differential inclusion Fixed point Integral solutions Extremal solution ControllabilityIn this paper, we shall establish sufficient conditions for the existence of integral solutions and extremal integral solutions for some nondensely defined impulsive semilinear functional differential inclusions in separable Banach spaces. We shall rely on a fixed point theorem for the sum of completely continuous and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
85
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 38 publications
0
85
0
Order By: Relevance
“…In the paper [1], Benchohra et al established sufficient conditions for the existence of mild and extremal mild solutions of first order impulsive functional evolution equations in a separable Banach space (X. |·|) of the form:…”
Section: Introductionmentioning
confidence: 99%
“…In the paper [1], Benchohra et al established sufficient conditions for the existence of mild and extremal mild solutions of first order impulsive functional evolution equations in a separable Banach space (X. |·|) of the form:…”
Section: Introductionmentioning
confidence: 99%
“…During the last ten years, impulsive differential equations and inclusions with different conditions have been intensely studied by many mathematicians, see [1,10,20]. At present, the foundations of the general theory are already laid, and many of them are formulated in detail in Benchohra et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…From the mathematical point of view, the problems of exact and approximate controllability are to be distinguished. Exact controllability enables to steer the system to arbitrary final state (see for example [1,5,18,20]) while approximate controllability means that system can be steered an arbitrary small neighborhood of final state. Approximately controllability systems are more prevalent and very often approximate controllability is completely adequate in applications.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that the density condition is not necessary for dealing with the existence of integral solutions and the controllability for many classes of both the functional differential equations (see [7], [5], [8]) and the semilinear functional differential inclusions (see [1], [2], [6]). …”
Section: Introductionmentioning
confidence: 99%